We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
134
2
avatar+844 

for this i made \(R= \begin{pmatrix} p-6\\ 5-2p \end{pmatrix}\)

since r is paralel to \(\begin{pmatrix} 1\\ -3 \end{pmatrix}\)

i did 1= K(p-6) and -3= K(5-2p)

and through simultaneous equation i got k =7 

but it was obvious that it is wrong please help thanks

 Feb 23, 2019

Best Answer 

 #1
avatar+5782 
+1

\(R=F_1+F_2 = (p-6)\hat{i} + (5-2p)\hat{j}\\ \text{This is parallel to the vector }\hat{i} - 3\hat{j}\\ \text{The easiest way to do this is just to equate the slopes}\\ \dfrac{5-2p}{p-6}=\dfrac{-3}{1} \\ 5-2p = 18-3p\\ p = 13\)

 

\(R = (7,-21) \text{ which is clearly parallel to }(1,-3)\)

.
 Feb 23, 2019
 #1
avatar+5782 
+1
Best Answer

\(R=F_1+F_2 = (p-6)\hat{i} + (5-2p)\hat{j}\\ \text{This is parallel to the vector }\hat{i} - 3\hat{j}\\ \text{The easiest way to do this is just to equate the slopes}\\ \dfrac{5-2p}{p-6}=\dfrac{-3}{1} \\ 5-2p = 18-3p\\ p = 13\)

 

\(R = (7,-21) \text{ which is clearly parallel to }(1,-3)\)

Rom Feb 23, 2019
 #2
avatar+844 
+1

thank you very much!

YEEEEEET  Feb 23, 2019

5 Online Users